Labyrinthine haemorrhage secondary to cerebral venous thrombosis. (12th November 2021) - Martins, Ana Inês; Figueiredo, Carlos; Melancia, Diana; Jorge, André; Amorim, Ana Margarida; Pereira, Daniela; Nunes, César; Silva, Fernando; Lemos, João
Abstract: Cerebral venous thrombosis (CVT) can rarely present with acute ipsilateral cochlear and/or vestibular loss, to date always in the absence of a clear local otogenic process evidenced by magnetic resonance imaging (MRI). This association has been putatively attributed to inner ear anoxia due to blockage of inner ear venous drainage. We present a nonreported case of thrombosis of the left transverse and sigmoid sinuses presenting with acute unilateral vestibulopathy in which MRI disclosed concurrent ipsilateral labyrinthine haemorrhage. A 69‐year‐old female presented with acute vertigo without hearing loss or other accompanying neurological symptoms. Bedside examination revealed spontaneous right‐beating nystagmus and an impaired left head impulse response, with an otherwise normal neurological examination. Audiometry and head and ear computed tomography were unremarkable, whereas MRI showed a nonenhancing hyperintensity of the left inner ear consistent with labyrinthine haemorrhage, and additional venography disclosed thrombosis of the left transverse and sigmoid sinuses. Oral anticoagulation was started, and the patient experienced gradual improvement of symptoms. The current case provides support for the existence of inner ear anoxia in CVT cases presenting with acute ipsilateral vestibular loss, which can ultimately be complicated by secondary bleeding, as seen in our patient. Importantly, presentation in our case closely mimicked that of peripheral vestibular neuritis, and only MRI venography enabled us to make a prompt diagnosis. This raises an important question as to when a diagnosis of vestibular neuritis can be made securely in the absence of MRI assessment with or without venography to completely discard labyrinthine haemorrhage with or without CVT. Abstract : Cerebral venous thrombosis (CVT) may rarely manifest with labyrinthine haemorrhage (LH). LH associated with CVT may reflect haemorrhagic transformation of an ischaemic process. A normal brain and ear computed tomography scan in a patient with acute unilateral vestibulopathy does not rule out LH.